THE ROLE OF RELIGION IN THE FORMATION OF NATIONAL IDENTITY AMONG SERBS FROM KOSOVO AND METOHIJA (Heritage, 2021)
The history of Balkan states shows that religion in its essence has been a main factor of differentiation of numerous national communities and key to the formation of nations on Balkan soil. This testifies to the great importance of religion in this area. Religion has influenced the separation of nations and the creation of different national identity.Orthodoxy has always been of a great importance to Serbs. However, religion, as already mentioned, was significantly limited an emphasized by politics throughout history depending on the political agendas of that time.The end of the 20th and the beginning of the 21th century brought a large number of challenges for Serbia which jeopardized its national identity. The political ruling forces in Serbia have turned to religion as an element that can, without any doubt, influence on the strengthening national identity.Taking into account developments in Kosovo and Metohija during the last decades, the need for strong national identity and sense of belonging has been more important than ever. From that need arise the process of turning to religion as a way to preserve traditions and customs that have been threatened by other nations and identities.In the specific context of Kosovo it is important to keep in mind that religion is precisely the element that has sustained Serbs as a national group in these territories. Through religion, the permanence of the Serbian nation is manifested and proved day by day, not only in the territory of Kosovo and Metohija, but also in the rest of Serbia in order to maintain the spirit and morale of those who fled and left their homes.
Keywords: religion, national identity, Balkans, Kosovo and Metohija